Tafsir juz 'Amma / Syaikh 'Abdullah al-Khayyath; penerjemah, Herman Susilo; editor, Syariful Mahya Lubis - AL-KHAYYATH, 'Abdullah , Syaikh; Herman Susilo; LUBIS, Syariful Mahya (Griya Ilmu, 2016)
xvi, 219 hlm. : ilus. ; 24 cm.